Repetitive strain injury (RSI) in guitarist: causes, effects and preventions / Ronny Philip - Philip, Ronny (2011)
This study was carried out to determine the causes and effects of Repetitive Strain Injury (RSI) in guitarist. Two male guitarists with previous history of Performance Arts Injures were chosen to be the respondents of this study. A set of question was designed to gain primary data from the respondents. Secondary data were collected from journals, websites and articles with the same topic. The overall findings of the study indicate that misuse and overuse of body parts are some of the main causes of RSI in guitarist. In conclusion, some suggestions have been made to minimize the development of RSI in guitarist and recommendations for future research have also been included in the final parts of the report.